Elevated Red Cell Distribution Width Is Independently Associated With a Higher Frailty Risk Among 2,932 Community-Dwelling Older Adults - Li, Chia-Ming; Chao, Chia-Ter; Chen, Shih-I; Han, Der-Sheng; Huang, Kuo-Chin (Frontiers in Medicine, 2020)
Background: Older adults are at an increased risk of frailty, but laboratory surrogates for identifying frailty in this population remain controversial and clinicians frequently encounter difficulty during frailty screening. We examined whether high red cell distribution width (RDW) was associated with an increased probability of frailty in older adults. Methods: We prospectively included community-dwelling older adults between 2013 and 2016 from a single institute, with their clinical features/laboratory parameters documented. We used the Study of Osteoporotic Fractures index (malnutrition, poor physical performance, and fatigue) to delineate frailty, and harnessed multiple logistic regression to investigate whether having a high RDW (≥ 15.7%) was associated with an increased risk of having frailty among these participants Results: A total of 2932 older adults (mean 73.5 ± 6.7 years; 44.6% male) were included, among whom 113 (3.9%) and 76 (2.6%) had a high RDW and presented frailty, respectively. Older adults with a high RDW were more likely to be frail (p = 0.002) and had more positive SOF items than those with normal RDW levels (p = 0.013). Those with a high RDW exhibited a significantly higher risk of having frailty (odds ratio [OR] 2.689, 95% confidence interval [CI] 1.184 – 6.109) compared to those without. Sensitivity analyses using RDW as a continuous variable similarly showed that RDW levels were positively associated with frailty risk (OR 1.223 per 1% RDW higher). Conclusions: In older adults, higher RDW can be regarded as a frailty indicator, and the readiness in RDW assessment supports its screening utility.